2017
DOI: 10.1097/md.0000000000005532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperthermic intrathoracic chemotherapy (HITHOC) on the malignant pleural effusion

Abstract: Background:Although hyperthermic intraperitoneal chemotherapy (HIPEC) has been widely used to treat malignant ascites or as a preventive strategy for microscopic carcinomatosis following surgical resection of abdominal tumors, application of hyperthermic intrathoracic chemotherapy (HITHOC) in the treatment of malignant pleural effusion is limited. The objective of the current study was to conduct a systematic review and meta-analysis on the application of HITHOC in the palliative treatment of malignant pleural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
0
40
0
6
Order By: Relevance
“…Zur Anwendung der HITOC bei der sekundären Pleurakarzinose kann auf der Basis der Expertenmeinung nur eine offene Empfehlung ausgesprochen werden, da nur sehr wenig Daten und Erfahrungen vorhanden sind [26,34] (vgl. ▶ Tab.…”
Section: Schutzmaßnahmenunclassified
“…Zur Anwendung der HITOC bei der sekundären Pleurakarzinose kann auf der Basis der Expertenmeinung nur eine offene Empfehlung ausgesprochen werden, da nur sehr wenig Daten und Erfahrungen vorhanden sind [26,34] (vgl. ▶ Tab.…”
Section: Schutzmaßnahmenunclassified
“…For this reason, on the basis of our recent experience with cytoreductive surgery and hyperthermic intrathoracic chemotherapy (HITHOC) for mesothelioma and malignant pleural effusion [2,3], and some recent publications reporting good survival in selected patients with stage IVA lung cancer [4][5][6], we strongly believe that not all patients with stage IVA (M1a) NSCLC are the same and that longer survival can be obtained in those with disease confined in the hemithorax, and therefore a "new" form of precision (individualised) surgery should be explored as part of a multidisciplinary treatment modality. ZHOU et al [7] performed a meta-analysis on the effect of debulking surgery and HITHOC on malignant pleural effusion for various primary cancers. They showed that patients who received HITHOC had a significantly longer survival.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that patients who received HITHOC had a significantly longer survival. ZHOU et al [7] concluded that HITHOC is safe, effective and increases the survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…Diese intraoperative Perfusion kann in einer palliativen Situation erfolgen, meistens wird jedoch ein potenziell kurativer Therapieansatz nach möglichst kompletter peritonealer bzw. pleuraler chirurgischer Tumorresektion verfolgt [3,4].…”
Section: Introductionunclassified